Comparison between Artificial Bee Colony and Particle Swarm Optimization algorithms in the tuning of PSS and UPFC-POD controllers - Martins, Luis Fabiano B.; Gamino, Bruno R. [UNESP]; De Araujo, Percival B. [UNESP]; Fortes, Elenilson De V.; Miotto, Ednei L. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
In this work, the Artificial Bee Colony and Particle Swarm Optimization algorithms are used to tune supplementary damping controllers (Power System Stabilizers and Unified Power Flow Controller-Power Oscillation Damping). These controllers are inserted into a test system with the aim of introducing supplementary damping to low-frequency oscillation modes. A design for current injections of the UPFC device is suggested and incorporated into the Current Sensitivity Model, which represents the Electric Power System. The performance of Artificial Bee Colony and Particle Swarm Optimization algorithms are compared by simulations in the test system. The results obtained using these methodologies suggest that the Artificial Bee Colony algorithm has a superior performance in the solution of the proposed problem, demonstrating its usefulness as a tool in the analysis of small signal stability.
Keywords: Artificial Bee Colony; Particle Swarm Optimization; Power Oscillation Damping; Power Systems Stabilizers; Unified Power Flow Controller